2021
DOI: 10.3390/ijms22052733
|View full text |Cite
|
Sign up to set email alerts
|

Flowering and Seed Production across the Lemnaceae

Abstract: Plants in the family Lemnaceae are aquatic monocots and the smallest, simplest, and fastest growing angiosperms. Their small size, the smallest family member is 0.5 mm and the largest is 2.0 cm, as well as their diverse morphologies make these plants ideal for laboratory studies. Their rapid growth rate is partially due to the family’s neotenous lifestyle, where instead of maturing and producing flowers, the plants remain in a juvenile state and continuously bud asexually. Maturation and flowering in the wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…Protandry is thought to reduce self-pollination, thereby contributing to the genetic diversity of a species (Lloyd and Webb, 1986). Examples of protandry and protogyny (the female phase proceeds the male phase) occur in Lemnoideae plants (Fourounjian et al, 2021). Our observations suggested that L. aequinoctialis develops two stamens, one of which grows longer; the longer stamen becomes exposed outside the frond, but, in our culture conditions, the shorter stamen often was not displayed (Figures 2E-H).…”
Section: Aequinoctialis Frond and Floral Developmentmentioning
confidence: 63%
See 1 more Smart Citation
“…Protandry is thought to reduce self-pollination, thereby contributing to the genetic diversity of a species (Lloyd and Webb, 1986). Examples of protandry and protogyny (the female phase proceeds the male phase) occur in Lemnoideae plants (Fourounjian et al, 2021). Our observations suggested that L. aequinoctialis develops two stamens, one of which grows longer; the longer stamen becomes exposed outside the frond, but, in our culture conditions, the shorter stamen often was not displayed (Figures 2E-H).…”
Section: Aequinoctialis Frond and Floral Developmentmentioning
confidence: 63%
“…The timing of stamen and pistil maturation differs among species in the Lemnoideae. Stamen maturation proceeds pistil maturation in some Lemnoideae plants, whereas the opposite timing occurs in others (Fourounjian et al, 2021). In L. aequinoctialis, stamens appear first (Figure 2E), then pistils appear (Figure 2F).…”
Section: Lemna Aequinoctialis Flower Developmentmentioning
confidence: 97%
“…We tried to verify if the hybrid clones that we have identified could correspond to putative 'L. symmeter' on these criteria, by inducing flowering through treatment with salicylic acid (SA) as reported by others [33,34]. After four weeks of cultivation in 20 µM SA, we were able to induce flowering in two out of three L. gibba clones (7742a and 9598, not 8124), but neither the six hybrid clones, nor two L. minor clones (9977 and 9942) showed reproductive organs after six weeks.…”
Section: Frond Morphology and Floweringmentioning
confidence: 95%
“…Flowers are composed of one stamen with the anther and a pistil within which there is one atropous ovule [13]. Recently, laboratory protocols were developed to control flowering in W. microscopica [33]. Nevertheless, several aspects of the reproductive biology and ecology of Wolffia species are still unexplored.…”
Section: Plant Morphological and Reproductive Traitsmentioning
confidence: 99%